Preparation method of ethyl cellulose / acrylate composite resin
A method using a low eutectic solvent to produce high-purity ethyl cellulose for copper electronic paste in MLCC production addresses the thermal instability of ethyl cellulose, enhancing viscosity and ensuring complete decomposition for improved MLCC production.
Patent Information
- Application Number
- CN202411484537.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-10-23
AI Technical Summary
The oxidation characteristics of Cu electrodes in MLCC production require a nitrogen atmosphere for debinding and sintering, which copper electronic paste cannot achieve, leading to poor product quality due to unstable thermal decomposition and high thermal decomposition residue of ethyl cellulose used as a thickener, and the traditional synthesis of ethyl cellulose results in severe degradation and non-uniform molecular structure.
A method involving reacting wood pulp and ethyl halide in a low eutectic solvent composed of choline chloride, urea, and sodium hydroxide to produce ethyl cellulose, followed by extraction and precipitation to obtain high-purity ethyl cellulose, which is then compounded with polyacrylic acid resin to improve thermal stability and form a homogeneous state, and then melt-mixing the obtained ethyl cellulose/acrylate composite resin.
The method produces a composite resin with low thermal decomposition residue suitable for copper electronic paste, improving viscosity and rheological properties, ensuring complete decomposition without ash residue and facilitating MLCC production.
Smart Images

Figure CN119192761A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic capacitors, and in particular relates to a method for preparing an ethyl cellulose / acrylate composite resin. Background Art
[0002] Chip multilayer ceramic capacitors (MLCC) have important applications in mobile phones, audio equipment, and automobiles. They are increasingly showing a trend towards low power consumption, miniaturization, and high capacity. At present, in the MLCC production process, Cu electrodes with good conductivity are gradually replacing precious metal electrodes to become the mainstream research direction. However, the oxidation characteristics of Cu mean that the debinding and sintering process of electronic paste can only be carried out in a nitrogen atmosphere. Domestic MLCC copper electronic paste must be humidified during the debinding stage to promote the thermal decomposition and debinding of the organic carrier. It faces the actual production problem that copper electronic paste cannot complete debinding and good sintering in a nitrogen atmosphere, which seriously affects product quality.
[0003] Ethyl cellulose (EC) is the ethyl ether of cellulose, which has good wetting, bonding, and film-forming effects. It is widely used as a thickener in the preparation of silver electronic paste. However, in copper electronic paste, EC has problems such as unstable thermal decomposition performance, high thermal decomposition residue, and poor debinding and sintering process. The main reason is that in the traditional process of synthesizing EC using toluene as solvent and sodium hydroxide as catalyst system, cellulose is severely degraded due to the strong alkaline environment; moreover, due to the heterogeneous reaction, the substitution reaction is not uniform, the product molecular structure is quite different, the molecular weight and molecular weight distribution are difficult to control, and the solubility and thermal decomposition performance are greatly affected; at the same time, the reaction product EC and the cellulose raw material are difficult to separate, resulting in a relatively complicated post-processing process.
[0004] Therefore, solving the problems of thermal decomposition residue and debinding of organic carriers of copper electronic slurries with EC as thickener has important production significance and practical value. Summary of the invention
[0005] The purpose of the present invention is to overcome the problems existing in the above-mentioned prior art and provide a method for preparing an ethyl cellulose / acrylate composite resin.
[0006] The present invention is achieved through the following technical solutions:
[0007] The object of the present invention is to provide a method for preparing an ethyl cellulose / acrylate composite resin, comprising the following steps: reacting wood pulp and ethyl halide in a low eutectic solvent (DES), extracting, and precipitating to obtain ethyl cellulose; and then melt-mixing the obtained ethyl cellulose with a polyacrylic acid resin to obtain the ethyl cellulose / acrylate composite resin; the low eutectic solvent comprises choline chloride, urea, and sodium hydroxide.
[0008] The present invention reacts wood pulp and ethyl halide in a low eutectic solvent containing choline chloride, urea and sodium hydroxide to obtain ethyl cellulose, then extracts, separates the unreacted pulp and low-substituted ethyl cellulose from the high-substituted ethyl cellulose product, and then precipitates to remove low-molecular-weight ethyl cellulose to obtain high-purity ethyl cellulose. It is then compounded with polyacrylic acid resin. After the polyacrylate is dissolved by the solvent, the viscosity of the electronic paste can be effectively improved, and it has certain rheological properties. After printing, the paste can maintain a good shape and form a hard film, and it can be completely decomposed without leaving ash in the debinding and sintering stage. The ethyl cellulose / acrylate composite resin finally obtained by the present invention can be directly used as an organic carrier of copper electronic paste in the MLCC tape casting process.
[0009] Preferably, the degree of polymerization of the wood pulp is 350-850. More preferably, the degree of polymerization of the wood pulp is 400-800.
[0010] If the degree of polymerization of wood pulp is too high, the reaction will be difficult, and if the degree of polymerization is too low, the performance will be poor. Therefore, wood pulp with a degree of polymerization of 350-850 is preferred.
[0011] The present invention does not limit the raw material source and preparation method of wood pulp. For example, the wood pulp can be coniferous wood pulp or hardwood wood pulp, and the preparation method can be, for example, a sulfate process.
[0012] Preferably, the wood pulp has an α-cellulose content of >90%, an ash content of ≤0.1%, and a lignin content of <1%.
[0013] Preferably, the mass ratio of the wood pulp to the volume ratio of the ethyl halide is 1 g: (4-6) mL.
[0014] Preferably, the ethyl halide comprises ethyl bromide.
[0015] Preferably, the mass ratio of the wood pulp to the low eutectic solvent is 1:(8-15).
[0016] Preferably, in the low eutectic solvent, the mass ratio of choline chloride, urea and sodium hydroxide is 1:(2-3):(1.5-5).
[0017] Preferably, the reaction temperature is 100°C-130°C, and the reaction time is 0.5h-3h.
[0018] Preferably, the reaction is carried out with stirring under closed conditions.
[0019] Preferably, the extractant used in the extraction comprises toluene.
[0020] Preferably, the precipitant used in the precipitation comprises diethyl ether.
[0021] The present invention uses the strong solubility and catalytic performance of DES to make cellulose react with ethyl halide in a homogeneous state in a dissolved state, and the obtained product has good structural uniformity and low cellulose degradation. After the reaction is carried out to a certain extent, an extractant such as toluene, a good solvent of EC, is added for extraction, and high-substitution EC is transferred from the strong polar DES to toluene. Since cellulose and low-substitution EC are insoluble in toluene, the product purity is high and the substitution degree is relatively high. A precipitant such as ether is added to toluene, so that the high molecular weight product is precipitated and then separated from part of the low molecular weight product. The ether and toluene used in the process can be recycled and applied. There is no special requirement for the amount of ether added as a precipitant, and ether is added to the organic solvent until no precipitate continues to precipitate.
[0022] Preferably, the temperature is lowered to 70° C.-90° C. before extraction, and the organic solvent is added and stirred sufficiently to fully extract the ethyl cellulose into the organic phase.
[0023] Preferably, the mass ratio of the low eutectic solvent to the volume ratio of the extractant is 1 g: (1-3) mL.
[0024] Preferably, the mass ratio of the ethyl cellulose to the polyacrylic acid resin is 1:(0.5-3).
[0025] The ethoxy content in the ethyl cellulose obtained by the invention is greater than 50%.
[0026] The present invention has the following beneficial effects:
[0027] The present invention uses wood pulp as a starting material, ethyl halide as a reaction reagent, and a choline chloride-urea-sodium hydroxide low eutectic solvent as a solvent and a catalyst. The wood pulp reacts with ethyl halide under the catalysis of DES to generate ethyl cellulose (EC). After a certain degree of substitution, EC is precipitated from DES and gradually dissolved in an extractant, and an organic phase is separated. A precipitant is added to obtain EC with low thermal decomposition residue suitable for the MLCC process. The EC is compounded with a polyacrylic acid resin to obtain a mixed resin with excellent molding effect, low thermal decomposition residue, and good debinding effect, which can be used as an organic carrier for the preparation of copper electronic paste in the MLCC production process. The preparation method of the present invention is simple to operate, environmentally friendly, and easy to realize industrial production. The DES after separating the organic phase can be continuously used, and both the solvent and the precipitant can be reused, which can reduce production costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is the thermal decomposition residue curve of the ethyl cellulose / acrylate composite resin prepared in Example 2;
[0029] Figure 2 is a photograph of the ethyl cellulose / acrylate composite resin prepared in Example 3;
[0030] Figure 3 Comparison of thermal decomposition residue curves of the ethyl cellulose / acrylate composite resin prepared in Example 7 and different solvents. DETAILED DESCRIPTION
[0031] To better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be understood by those skilled in the art that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0032] Unless otherwise specified, the experimental methods used in the examples are all conventional methods; the materials, reagents, etc. used, unless otherwise specified, can be obtained from commercial channels.
[0033] The raw materials of softwood pulp and hardwood pulp described in the embodiments of the present invention are prepared by the kraft process. The polyacrylic acid resin is Degussa solid acrylic resin DEGALAN LP65 / 12.
[0034] Example 1
[0035] A method for preparing an ethyl cellulose / acrylate composite resin comprises the following steps:
[0036] 5 g of softwood pulp with a degree of polymerization of 500, 25 mL of ethyl bromide and 50 g of a low eutectic solvent were mixed, sealed, heated to 110°C and stirred for 1 h, cooled to 80°C and injected with 50 mL of toluene, and stirred for 0.5 h. The organic phase was separated and dried over anhydrous sodium sulfate, and 4.3 g of ethyl cellulose was precipitated by adding ether;
[0037] Then, 2 g of the obtained ethyl cellulose and 3 g of polyacrylic acid resin were melt-blended at 180° C., cooled, and crushed to obtain the ethyl cellulose / acrylate composite resin.
[0038] The coniferous wood pulp has an alpha-cellulose content of 96%, an ash content of 0.1%, and a lignin content of less than 1%; the low eutectic solvent consists of choline chloride, urea and sodium hydroxide, and the mass ratio of choline chloride, urea and sodium hydroxide is 1:2:3.
[0039] According to tests, the thermal decomposition residue of the obtained ethyl cellulose / acrylate composite resin at 900° C. is less than 0.3%.
[0040] Example 2
[0041] A method for preparing an ethyl cellulose / acrylate composite resin comprises the following steps:
[0042] 5 g of softwood pulp with a degree of polymerization of 400, 25 mL of ethyl bromide and 50 g of a low eutectic solvent were mixed, sealed, heated to 110°C and stirred for 1 h, cooled to 80°C and injected with 50 mL of toluene, and stirred for 0.5 h. The organic phase was separated and dried over anhydrous sodium sulfate, and 4.5 g of ethyl cellulose was precipitated by adding ether;
[0043] Then, 2 g of the obtained ethyl cellulose and 4 g of polyacrylic acid resin were melt-blended at 180° C., cooled, and crushed to obtain the ethyl cellulose / acrylate composite resin.
[0044] The coniferous wood pulp has an alpha-cellulose content of 96%, an ash content of 0.1%, and a lignin content of less than 1%; the low eutectic solvent consists of choline chloride, urea and sodium hydroxide, and the mass ratio of choline chloride, urea and sodium hydroxide is 1:2:3.
[0045] According to the test, the thermal decomposition residue of the obtained ethyl cellulose / acrylate composite resin at 900°C is less than 0.2%. Figure 1 : is the thermal decomposition residue curve of the ethyl cellulose / acrylate composite resin prepared in this example.
[0046] Example 3
[0047] A method for preparing an ethyl cellulose / acrylate composite resin comprises the following steps:
[0048] 5 g of softwood pulp with a degree of polymerization of 600, 25 mL of ethyl bromide and 60 g of a low eutectic solvent were mixed, sealed, heated to 110°C and stirred for 1 h, cooled to 80°C and injected with 70 mL of toluene, and stirred for 0.5 h. The organic phase was separated, dried over anhydrous sodium sulfate, and 4.4 g of ethyl cellulose was precipitated by adding diethyl ether;
[0049] Then, 2 g of the obtained ethyl cellulose and 6 g of polyacrylic acid resin were melt-blended at 180° C., cooled, and crushed to obtain the ethyl cellulose / acrylate composite resin.
[0050] The coniferous wood pulp has an alpha-cellulose content of 96%, an ash content of 0.1%, and a lignin content of less than 1%; the low eutectic solvent consists of choline chloride, urea and sodium hydroxide, and the mass ratio of choline chloride, urea and sodium hydroxide is 1:2:3.
[0051] Figure 2 This is a photo of the ethyl cellulose / acrylate composite resin prepared in this example. According to tests, the thermal decomposition residue of the obtained ethyl cellulose / acrylate composite resin at 900° C. is less than 0.35%.
[0052] Example 4
[0053] A method for preparing an ethyl cellulose / acrylate composite resin comprises the following steps:
[0054] 5 g of softwood pulp with a degree of polymerization of 600, 25 mL of ethyl bromide and 75 g of a low eutectic solvent were mixed, sealed, heated to 110°C and stirred for 1 h, cooled to 80°C and injected with 80 mL of toluene, and stirred for 0.5 h. The organic phase was separated and dried over anhydrous sodium sulfate, and 4.6 g of ethyl cellulose was precipitated by adding ether;
[0055] Then, 2 g of the obtained ethyl cellulose and 6 g of polyacrylic acid resin were melt-blended at 180° C., cooled, and crushed to obtain the ethyl cellulose / acrylate composite resin.
[0056] The coniferous wood pulp has an alpha-cellulose content of 96%, an ash content of 0.1%, and a lignin content of less than 1%; the low eutectic solvent consists of choline chloride, urea and sodium hydroxide, and the mass ratio of choline chloride, urea and sodium hydroxide is 1:2:3.
[0057] According to tests, the thermal decomposition residue of the obtained ethyl cellulose / acrylate composite resin at 900° C. is less than 0.35%.
[0058] Example 5
[0059] A method for preparing an ethyl cellulose / acrylate composite resin comprises the following steps:
[0060] 5 g of softwood pulp with a degree of polymerization of 600, 25 mL of ethyl bromide and 40 g of a low eutectic solvent were mixed, sealed, heated to 110°C and stirred for 1 h, cooled to 80°C and injected with 50 mL of toluene, and stirred for 0.5 h. The organic phase was separated and dried over anhydrous sodium sulfate, and 4.1 g of ethyl cellulose was precipitated by adding ether;
[0061] Then, 2 g of the obtained ethyl cellulose and 2 g of polyacrylic acid resin were melt-blended at 180° C., cooled, and crushed to obtain the ethyl cellulose / acrylate composite resin.
[0062] The coniferous wood pulp has an alpha-cellulose content of 93%, an ash content of 0.1%, and a lignin content of less than 1%; the low eutectic solvent consists of choline chloride, urea and sodium hydroxide, and the mass ratio of choline chloride, urea and sodium hydroxide is 1:2:4.
[0063] According to tests, the thermal decomposition residue of the obtained ethyl cellulose / acrylate composite resin at 900° C. is less than 0.7%.
[0064] Example 6
[0065] A method for preparing an ethyl cellulose / acrylate composite resin comprises the following steps:
[0066] 5 g of softwood pulp with a degree of polymerization of 700, 25 mL of ethyl bromide and 60 g of a low eutectic solvent were mixed, sealed, heated to 110°C and stirred for 1 h, cooled to 80°C and injected with 60 mL of toluene, and stirred for 0.5 h. The organic phase was separated, dried over anhydrous sodium sulfate, and 3.8 g of ethyl cellulose was precipitated by adding diethyl ether;
[0067] Then, 3 g of the obtained ethyl cellulose and 2 g of polyacrylic acid resin were melt-blended at 180° C., cooled, and crushed to obtain the ethyl cellulose / acrylate composite resin.
[0068] The coniferous wood pulp has an alpha-cellulose content of 93%, an ash content of 0.1%, and a lignin content of less than 1%; the low eutectic solvent consists of choline chloride, urea and sodium hydroxide, and the mass ratio of choline chloride, urea and sodium hydroxide is 1:2:4.
[0069] According to tests, the thermal decomposition residue of the obtained ethyl cellulose / acrylate composite resin at 900° C. is less than 0.8%.
[0070] Example 7
[0071] A method for preparing an ethyl cellulose / acrylate composite resin comprises the following steps:
[0072] 5 g of softwood pulp with a degree of polymerization of 800, 25 mL of ethyl bromide and 70 g of a low eutectic solvent were mixed, sealed, heated to 110°C and stirred for 1 h, cooled to 80°C and injected with 90 mL of toluene, and stirred for 0.5 h, and the organic phase was separated, dried over anhydrous sodium sulfate, and 4.0 g of ethyl cellulose was precipitated by adding ether;
[0073] Then, 4 g of the obtained ethyl cellulose and 2 g of polyacrylic acid resin were melt-blended at 180° C., cooled, and crushed to obtain the ethyl cellulose / acrylate composite resin.
[0074] The coniferous wood pulp has an alpha-cellulose content of 93%, an ash content of 0.1%, and a lignin content of less than 1%; the low eutectic solvent consists of choline chloride, urea and sodium hydroxide, and the mass ratio of choline chloride, urea and sodium hydroxide is 1:2:4.
[0075] According to tests, the thermal decomposition residue of the obtained ethyl cellulose / acrylate composite resin at 900° C. is less than 1%. Figure 3 The thermal decomposition residue curves of the ethyl cellulose / acrylate composite resin prepared in this example and in different solvents are compared. Figure 3 It can be seen that the composite resin decomposes rapidly around 400 degrees Celsius, and the thermal decomposition residue at 900 degrees Celsius is less than 1%.
[0076] Example 8
[0077] A method for preparing an ethyl cellulose / acrylate composite resin comprises the following steps:
[0078] 5 g of hardwood pulp with a degree of polymerization of 800, 25 mL of ethyl bromide and 70 g of a low eutectic solvent were mixed, sealed, heated to 110°C and stirred for 1 h, cooled to 80°C and injected with 90 mL of toluene, and stirred for 0.5 h, and the organic phase was separated, dried over anhydrous sodium sulfate, and 3.6 g of ethyl cellulose was precipitated by adding diethyl ether;
[0079] Then, 3 g of the obtained ethyl cellulose and 3 g of polyacrylic acid resin were melt-blended at 180° C., cooled, and crushed to obtain the ethyl cellulose / acrylate composite resin.
[0080] The coniferous wood pulp has an alpha-cellulose content of 93%, an ash content of 0.1%, and a lignin content of less than %. The low eutectic solvent consists of choline chloride, urea, and sodium hydroxide, and the mass ratio of choline chloride, urea, and sodium hydroxide is 1:2:4.
[0081] According to tests, the thermal decomposition residue of the obtained ethyl cellulose / acrylate composite resin at 900° C. is less than 1%.
[0082] Comparative Example 1
[0083] A method for preparing a composite resin comprises the following steps:
[0084] 5 g of softwood pulp with a degree of polymerization of 400, 25 mL of ethyl bromide and 50 g of a low eutectic solvent were mixed, sealed, heated to 110°C and stirred for 1 h, cooled to 80°C and injected with 50 mL of toluene, and stirred for 0.5 h. The organic phase was separated and dried over anhydrous sodium sulfate, and 4.5 g of ethyl cellulose was precipitated by adding ether;
[0085] Then, 2 g of the obtained ethyl cellulose and 4 g of polybutyl acrylate resin were melt-blended at 180° C., cooled, and crushed to obtain the composite resin.
[0086] The coniferous wood pulp has an alpha-cellulose content of 96%, an ash content of 0.1%, and a lignin content of less than 1%; the low eutectic solvent consists of choline chloride, urea and sodium hydroxide, and the mass ratio of choline chloride, urea and sodium hydroxide is 1:2:4.
[0087] According to tests, the thermal decomposition residue of the obtained composite resin at 900° C. is less than 3% and greater than 2%.
[0088] Comparative Example 2
[0089] A method for preparing an ethyl cellulose / acrylate composite resin comprises the following steps:
[0090] The ethyl cellulose was prepared by a traditional method, which was as follows: 5 g of crushed cotton fiber was added into a reactor, vacuumed and filled with nitrogen, 20 mL of 50% liquid alkali and 60 mL of toluene were added, and alkalization reaction was carried out at 45°C for 0.5 h. After the alkalization was completed, 120 mL of ethyl chloride was added, and etherification was carried out at 120°C with stirring for 12 h. Acetic acid was neutralized to a pH of about 9, and the ethyl cellulose was filtered after repeated washing, and dried at 60°C to obtain ethyl cellulose;
[0091] Then, 2 g of the obtained ethyl cellulose and 4 g of polyacrylic acid resin were melt-blended at 180° C., cooled, and crushed to obtain the ethyl cellulose / acrylate composite resin.
[0092] According to tests, the thermal decomposition residue of the obtained ethyl cellulose / acrylate composite resin at 900° C. is less than 6% and greater than 5%.
[0093] Comparative Example 3
[0094] A method for preparing an ethyl cellulose / acrylate composite resin comprises the following steps:
[0095] 5 g of softwood pulp with a degree of polymerization of 400, 25 mL of ethyl bromide and 50 g of a low eutectic solvent were mixed, sealed, heated to 110°C and stirred for 1 h, cooled to 80°C and injected with 50 mL of toluene, and stirred for 0.5 h. The organic phase was separated and dried over anhydrous sodium sulfate, and 4.5 g of ethyl cellulose was precipitated by adding ether;
[0096] Then, 2 g of the obtained ethyl cellulose and 4 g of polyacrylic acid resin were melt-blended at 180° C., cooled, and crushed to obtain the ethyl cellulose / acrylate composite resin.
[0097] The coniferous wood pulp has an alpha-cellulose content of 96%, an ash content of 0.1%, and a lignin content of less than 1%; the low eutectic solvent is composed of choline chloride and lactic acid in a mass ratio of 1:2.
[0098] According to tests, the thermal decomposition residue of the obtained ethyl cellulose / acrylate composite resin at 900° C. is less than 5% and greater than 4%.
[0099] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing an ethyl cellulose / acrylate composite resin, characterized in that: The following steps are involved: The wood pulp and ethyl halide are reacted, extracted and precipitated in a low eutectic solvent to obtain ethyl cellulose; the obtained ethyl cellulose is then melt-mixed with polyacrylic acid resin to obtain the ethyl cellulose / acrylate composite resin; the low eutectic solvent includes choline chloride, urea and sodium hydroxide.
2. The method for preparing the ethyl cellulose / acrylate composite resin according to claim 1, characterized in that: The polymerization degree of the wood pulp is 350-850.
3. The method for preparing the ethyl cellulose / acrylate composite resin according to claim 1, characterized in that: The mass ratio of the wood pulp to the volume ratio of the ethyl halide is 1 g: (4-6) mL.
4. The method for preparing the ethyl cellulose / acrylate composite resin according to claim 1, characterized in that: The mass ratio of the wood pulp to the low eutectic solvent is 1:(8-15).
5. The method for preparing the ethyl cellulose / acrylate composite resin according to claim 1, characterized in that: In the low eutectic solvent, the mass ratio of choline chloride, urea and sodium hydroxide is 1:(2-3):(1.5-5).
6. The method for preparing the ethyl cellulose / acrylate composite resin according to claim 1, characterized in that: The reaction temperature is 100°C-130°C, and the reaction time is 0.5h-3h.
7. The method for preparing the ethyl cellulose / acrylate composite resin according to claim 1, characterized in that: The extractant used in the extraction includes toluene.
8. The method for preparing the ethyl cellulose / acrylate composite resin according to claim 1, characterized in that: The precipitant used in the precipitation includes diethyl ether.
9. The method for preparing the ethyl cellulose / acrylate composite resin according to claim 1, characterized in that: The mass ratio of the low eutectic solvent to the volume ratio of the extractant is 1 g: (1-3) mL.
10. The method for preparing the ethyl cellulose / acrylate composite resin according to claim 1, characterized in that: The mass ratio of the ethyl cellulose to the polyacrylic acid resin is 1:(0.5-3).
Citation Information
Patent Citations
Method for separating three components of cellulose, hemicellulose and lignin in plant fiber raw materials
CN108660837A
Method for separating holocellulose in wood fibers by using choline deep-eutectic solvent
CN110804893A
Cellulose Derivatives
US20210155716A1
